Verification of the Functional Antioxidant Activity and Antimelanogenic Properties of Extracts of Poria cocos Mycelium Fermented with Freeze-Dried Plum Powder - Kyung-Yun Kang; Yun-Ho Hwang; Sung-Ju Lee; Ho-Yeol Jang; Seong-Gyeol Hong; Seul-Ki Mun; Su-Jin Kim; Jong-Jin Kim; Kuyng-Wuk Park; Kyoung-Sun Seo; Seung-Eon Ban; Seong-Woo Jin; et al. (International Journal of Biomaterials)
Here we examine the effects of extracts of Poria cocos mycelium fermented with freeze-dried plum powder (PPE) on the α-melanocyte stimulating hormone (α-MSH)-stimulated melanogenesis in cultured murine B16 melanoma cells (B16 cells), relative to the effects of Prunus extract. We found that an extract of Prunus fermentation showed significant inhibition of melanogenesis and tyrosinase activity with no effect on cell proliferation and was more active compared to Prunus extract alone. Furthermore, we confirmed that medium containing 3% Prunus was the optimal culture substrate for fermentation with Poria cocos. These results provide evidence that Prunus fermentation extract affects skin whiting in murine B16 melanoma cells (B16 cells). Prunus contains rutin, oxalic acid, succinic acid, and fumaric acid, which help in digestion and fatigue recovery. The rutin of Prunus mume is reported to have antioxidant and anti-inflammatory effects. Also, Prunus extract has a tyrosinase inhibitory activity for skin whiting through its antioxidant activity. Therefore, we believe the Prunus extract for Poria cocos fermentation can be provided as a potential mediator to induce skin whiting.